Active Emulsions Based on Alginate and Lemongrass/Citral Essential Oils: Effect of Encapsulating Agents on Physical and Antimicrobial Properties - Matiacevich, S; Alarcon-Moyano, J (Taylor and Francis Inc., 2019)
For the development of a natural antimicrobial additive based on natural compounds (AC) such as lemongrass essential oil and its active compound citral, encapsulating agents (EA) are required to incorporate it inside food matrixes. Therefore, the effects of type and concentration of EA (maltodextrin and modified-starch called Capsul®) on physical and antimicrobial properties of alginate-based and Lemongrass/citral emulsions were evaluated. Emulsions using different AC:EA ratios were prepared, measuring their antimicrobial (Escherichia coli and Listeria innocua) and physical properties. Antimicrobial activities were observed in all emulsions independently of AC:EA ratio and EA or AC types. However, color differences (ΔE2000) depended on AC:EA ratio and AC used. For both AC, samples with maltodextrin showed higher viscosity and physical stability than Capsul® samples, while the latter showed the highest oxidative stability. In conclusion, EA type affected both physical and oxidative stability of alginate-AC-emulsions; however, both EA could be used for the development of natural antimicrobial additives. © 2019, © 2019 Jessica Alarcón-Moyano and Silvia Matiacevich. Published with license by Taylor & Francis Group, LLC.